PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE MAKE A MATCH TERHADAP HASIL BELAJAR IPAS PADA SISWA KELAS V SEKOLAH DASAR - Melsya Putri Yuliandra; Erlisnawati, Eva Astuti Mulyani (STKIP Subang, 2026)
This study aims to determine the effect of Cooperative Learning Model type Make a Match on the learning outcomes of grade V elementary school students in the 2024/2025 academic year. This research is quantitative with the research method used is experimental research with the type of Quasi Experiment research using the research design Nonequivalent Control Group Design. Pretest-posttest control group design. Data collection techniques using tests in the form of multiple choice questions. The subjects of this study were class VA totaling 20 students as the experimental class and class VB totaling 20 students as the control class. Researchers implemented Cooperative Learning type Make a Match in the experimental class and conventional methods in the control class. The results showed that the hypothesis test conducted using the t-test obtained a significance value of Sig. (2-tailed) of 0.007 <0.05 then Ho is rejected and Ha is accepted. So it can be concluded that there is a significant difference between the two groups, namely the experimental class and the control class, which means that there is an effect of the cooperative learning model type make a match on the learning outcomes of IPAS in grade V elementary school students.